Genome-wide characterization and evolution analysis of miniature inverted-repeat transposable elements in Barley (Hordeum vulgare) - Li, Ruiying; Yao, Ju; Cai, Shaoshuai; Fu, Yi; Lai, Chongde; Zhu, Xiangdong; Cui, Licao; Li, Yihan (Frontiers in Plant Science, 2024)
Miniature inverted-repeat transposable elements (MITEs) constitute a class of class II transposable elements (TEs) that are abundant in plant genomes, playing a crucial role in their evolution and diversity. Barley (Hordeum vulgare), the fourth-most important cereal crop globally, is widely used for brewing, animal feed, and human consumption. However, despite their significance, the mechanisms underlying the insertion or amplification of MITEs and their contributions to barley genome evolution and diversity remain poorly understood. Through our comprehensive analysis, we identified 32,258 full-length MITEs belonging to 2,992 distinct families, accounting for approximately 0.17% of the barley genome. These MITE families can be grouped into four well-known superfamilies (Tc1/Mariner-like, PIF/Harbinger-like, hAT-like, and Mutator-like) and one unidentified superfamily. Notably, we observed two major expansion events in the barley MITE population, occurring approximately 12-13 million years ago (Mya) and 2-3 Mya. Our investigation revealed a strong preference of MITEs for gene-related regions, particularly in promoters, suggesting their potential involvement in regulating host gene expression. Additionally, we discovered that 7.73% miRNAs are derived from MITEs, thereby influencing the origin of certain miRNAs and potentially exerting a significant impact on post-transcriptional gene expression control. Evolutionary analysis demonstrated that MITEs exhibit lower conservation compared to genes, consistent with their dynamic mobility. We also identified a series of MITE insertions or deletions associated with domestication, highlighting these regions as promising targets for crop improvement strategies. These findings significantly advance our understanding of the fundamental characteristics and evolutionary patterns of MITEs in the barley genome. Moreover, they contribute to our knowledge of gene regulatory networks and provide valuable insights for crop improvement endeavors.